The Subtleties and Contrasts of the LeuO Regulator in Salmonella Typhi: Implications in the Immune Response - Guadarrama, Carmen; Villaseñor, Tomás; Calva, Edmundo (Frontiers in Immunology, 2014)
Salmonella are facultative intracellular pathogens. Salmonella infection occurs mainly by expression of two Salmonella pathogenicity Islands (SPI-1 and SPI-2). SPI-1 encodes transcriptional factors that participate in the expression of virulence factors encoded in the island. However, there are transcriptional factors encoded outside the island that also participate in the expression of SPI-1-encoded genes. Upon infection, bacteria are capable of avoiding the host immune response with several strategies that involve several virulence factors under the control of transcriptional regulators. Interestingly, LeuO a transcriptional global regulator which is encoded outside of any SPI, is proposed to be part of a complex regulatory network that involves expression of several genes that help bacteria to survive stress conditions and, also, induces the expression of porins that have been shown to be immunogens and can thus be considered as antigenic candidates for acellular vaccines. Hence, the understanding of the LeuO regulon implies a role of bacterial genetic regulation in determining the host immune response.